Endobronchial Ultrasound (EBUS) – Update 2017 - Darwiche, Kaid; Özkan, Filiz; Wolters, Celina; Eisenmann, Stephan (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Endobronchial ultrasound (EBUS) has revolutionized the diagnosis of lung cancer over the last decade. This minimally invasive diagnostic method has also become increasingly important in the case of other diseases such as sarcoidosis, thereby helping to avoid unnecessary diagnostic interventions. This review article provides an update regarding EBUS and discusses current and future developments of this method.Der endobronchiale Ultraschall (EBUS) hat im letzten Jahrzehnt die Lungenkrebsdiagnostik revolutioniert. Auch bei anderen Erkrankungen wie der Sarkoidose hat der Stellenwert dieses minimalinvasiven diagnostischen Verfahrens erheblich zugenommen und somit geholfen, unnötige diagnostische Operationen zu vermeiden. Dieser Übersichtsartikel stellt ein Update zum EBUS dar und erläutert die aktuellen und zukünftigen Entwicklungen dieses Verfahrens.